Assessing human pressure on wild food and forage tree species for designing effective conservation actions in West Africa Sahel region - Hien, Bossila Séraphin; Bondé, Loyapin; Da, Sié Sylvestre; Bognounou, Fidèle; Boussim, Issaka Joseph; Ouédraogo, Oumarou (Ethnobotany Research and Applications, 2021)
Background: High harvesting of Non-Timber Forest Products (NTFPs) for food and fodder supply leads many tree species to be vulnerable or endangered due to overexploitation. This study aimed to assess harvesting pressure on food and forage species and to understand how the socio-economic profile of people affects their perception on species state as well as on the impact of harvesting methods on species dynamics. Methods: Semi-structured ethnobotanical surveys were conducted near the active stakeholders involved in NTFPs harvesting - children, women, herders, and former actors (old persons >50 years old, both women and herders). Hundred and four (104) people from 4 ethnic groups were interviewed. We have calculated the overharvesting index (OI) based on three pressure parameters: Fidelity level of use (FL), Relative frequency of harvesting (FH) and Relative intensity of pruning (IP). The difference between respondent’s perceptions on species state was tested using logistic regression followed by analysis of variance of the model. Results: The overharvesting index (OI) showed that eight (8) species are overharvested of which the first three species are Pterocarpus erinaceus Poir (OI = 122.1%), Saba senegalensis (A. DC.) Pichon (OI = 100%) and Lannea microcarpa Engl. & K. Krause (OI = 97.4%). These overharvested species are generally exploited using destructive methods, especially branch pruning for leaves and/or fruits harvesting. Local people´s perception on species state was significantly influenced by the type of actors and their age (p<0.0001 for both). This suggests that specific awareness message considering socio-economic profiles of people need to be developed for a truth conservation impact on the field. 82.3% of respondents declared that harvesting methods have no significant impact on species state, revealing that most people are still using forest resources in traditional considerations. Conclusion: Raising awareness, based on scientific information highlighting the effects of harvesting methods on the regeneration and functional traits of NTFPs species, could contribute positively to changing people’s consideration of the sustainable use of species. Keywords: Harvesting methods, Local perception, NTFPs, Overharvesting, Stakeholders Résumé Contexte: La forte récolte de produits forestiers non ligneux (PFNL) pour l’alimentation et le fourrage rend de nombreuses espèces d’arbres vulnérables en raison de leur surexploitation. Cette étude vise à évaluer la pression de la récolte sur les espèces alimentaires et fourragères et à comprendre comment le profil socio-économique des personnes affecte leur perception sur l’état des espèces ainsi que sur l’impact des méthodes de récolte sur la dynamique des espèces. Méthodes: Des enquêtes ethnobotaniques basées sur un interview semi-structurée ont été menées auprès des acteurs actifs impliqués dans la récolte des PFNL (enfants, femmes, éleveurs) et des anciens acteurs (personnes agées >50 ans). 104 personnes de 4 groupes ethniques ont été interrogées. Nous avons calculé l’indice de surexploitation (OI) sur la base de trois paramètres de pression que sont le niveau de Fidélité d’utilisation (FL), la Fréquence relative de récolte (FH) et l’Intensité relative d’élagage (IP). En ce qui concerne la perception des répondants sur l’état des espèces, la différence entre les groupes a été testée à l’aide d’une regression logistique suivie d’une analyse de la variance du modèle. Résultats: L’indice de surexploitation (OI) a montré que huit (8) espèces sont surexploitées, dont les trois premières sont représentées par Pterocarpus erinaceus Poir. (OI = 122,1%), Saba senegalensis (A. DC.) Pichon (OI = 100%) et Lannea microcarpa Engl. & K. Krause (OI=97,4%). Ces espèces surexploitées sont généralement exploitées par des méthodes destructrices, notamment par l’élagage des branches pour la récolte des feuilles et/ou des fruits. La perception des populations locales sur l’état des espèces a été significativement influencée par le type d’acteur et l’âge (p<0,0001, respectivement). Cela suggère qu’un message de sensibilisation spécifique tenant compte des profils socio-economique des personnes doit être développé pour obtenir un impact large sur la conservation des espèces. 82,3% des personnes interrogées ont déclaré que les méthodes de récoltes n’ont pas d’impact significatif sur l’état des espèces, ce qui révèle que la majorité des gens continuent à exploiter les ressources forestières selon leurs considérations traditionnelles. Conclusion: La sensibilisation des populations, basée sur des informations scientifiques mettant en évidence les effets des méthodes de récolte sur la régénération des espèces de PFNL et leurs caractéristiques fonctionnelles, pourrait positivement contribuer à changer leur considération en faveur de l’utilisation durable des espèces. Mots-clés: Méthodes de récolte, Perception locale, PFNL, Surexploitation, Parties prenantes